THE ROLE NURSING IN FACE OF PALIATIVE CARE IN THE INTENSIVE CARE UNIT (REMUNOM, 2024)
Nursing plays a crucial role in the context of palliative care, especially in Intensive Care Units, highlighting the importance of interventions that not only aim to relieve physical suffering but also provide emotional and spiritual support to both patients and their families. Objective: To understand the role of the nursing team and nurses in palliative care in ICUs. Method: Integrative review, with a search for studies conducted in the BVS and SCIELO databases published in the last five years. Results: The synthesis of the selected studies allowed the categorization of three thematic axes and consequently identified thematic subcategories within these axes, which clarify the role of the nursing team in palliative care in ICUs. Conclusion: Therefore, the role of nursing in palliative care is not only to plan and provide care for the individual and their family, but also to enhance the quality of life and quality of death through the use of care technologies that reduce pain, promote comfort, and involve the family in the care process.